Penetration Testing For Dummies - Shimonski, Robert (--For dummies., 2020)
Target, test, analyze, and report on security vulnerabilities with pen testing Pen Testing is necessary for companies looking to target, test, analyze, and patch the security vulnerabilities from hackers attempting to break into and compromise their organizations data. It takes a person with hacking skills to look for the weaknesses that make an organization susceptible to hacking. Pen Testing For Dummies aims to equip IT enthusiasts at various levels with the basic knowledge of pen testing. It is the go-to book for those who have some IT experience but desire more knowledge of how to gather intelligence on a target, learn the steps for mapping out a test, and discover best practices for analyzing, solving, and reporting on vulnerabilities. The different phases of a pen test from pre-engagement to completion Threat modeling and understanding risk When to apply vulnerability management vs penetration testing Ways to keep your pen testing skills sharp, relevant, and at the top of the game Get ready to gather intelligence, discover the steps for mapping out tests, and analyze and report results!